MICROCIRCULATORY RESERVES AND TISSUE METABOLISM REACTIVITY IN VARIOUS STAGE ISCHEMIC CONGESTIVE HEART FAILURE - A. S. Klinkova; O. V. Kamenskaya (Российский кардиологический журнал)
Aim. To assess microcirculatory reserves and tissue metabolism reactivity in patients with coronary heart disease (CHD) with various stages of chronic heart failure (CHF).Material and methods. Totally, 112 CHD patients included. First group (45 persons) consisted of those with CHF I-II FC, second (67 persons) — CHF III-IV FC. By the method of laser-doppler flowmetry (LDF) we studied reserves of cutaneous microcirculatory blood flow (MBF) of lower extremities. Reactivity of tissue metabolism of lower extremities was assessed by transcutaneous oxymetry (ТсрО2 ). Using monofactorial logistic regression, we calculated predictors of adverse cardiovascular events in long-term period after coronary bypass operation (CBG).Results. MBF level between groups did not differ significantly. Reserves of capillary flow (RCF) in the 1st group were higher than 2nd — 169,1±2,25% and 147,3±2,46% from baseline, respectively, (p=0,01). Lowest efficacy of oxygen supply to peripheral tissues was found in 2nd group (p=0,03). Reserves of metabolic activity of tissues during postocclusion hyperemia — RTmО2 in 1st and 2nd groups were 143,2±2,24% and 125,4±2,86% from baseline, respectively, (p=0,01). Monofactorial logistic regression analysis revealed: 1) RCF lower 125% with 2 type diabetes do increase odds for surgically significant stenoses in lower limbs arteries after CBG in long-term perspective (OR 3,8; CI 1,9-6,5; p=0,002); 2) ejection fraction of the LV lower 40%, increased homocysteine >15,5 mcM/L and RTmО2 less than 120% do increase odds for stroke in long-term period after CBG (OR 4,1; CI 2,2-7,8; p=0,001).Conclusion. Relation of hypoxia in peripheral tissues at the background of LV dysfunction and hyperhomocysteinemia with development of stroke in long-term period after CBG, as baseline low RCF and DM 2 type with the development of lower limb arteries stenoses after CBG points on the necessity of emphasis on the assessment of microcirculatory reserves as one of leading vascular complications components.